The sacred-profane:: central events of San Pacho Festival in Quibdó-Chocó. (The Voz a Vos Bulletin, 2023)
Chronicle on the San Pacho´s celebration in 2023, of the experience and the great learning of this in its popular character. There are no restrictions for the attendance to the celebration moments or for the devotion events and it is a space in which the sacred is combined with pagan enjoyment.